Socialization of Laboratory Management and Screening of Sexually Transmitted Diseases in Pregnant Women at Aek Natolu Health Center - Nisa El Hasanah; Rahmadani Sitepu; Nur Afni Heryanti Octavia; Elsha Sinulingga; Surya Elisabet Hasibuan (JURNAL PENGMAS KESTRA (JPK), 2026)
A health laboratory is a healthcare facility that conducts examinations, analyses, and tests on human biological samples or non-biological materials to help identify diseases, determine the causes of health disorders, assess the health conditions of individuals or communities, and detect factors that can affect health status. Screening for sexually transmitted infections is a health check carried out to detect the presence of sexually transmitted infections in someone, even before symptoms appear, so that treatment can be done earlier to prevent complications and further transmission. For pregnant women, screening for sexually transmitted infections plays an important role in maintaining the health of both mother and baby and supporting efforts to reduce maternal and infant morbidity and mortality. The goal of this community service is to understand the relationship of health laboratory management in supporting sexual transmitted disease screening programs at pregnant women at Aek Natolu Health Center. The community service activity was carried out using a participatory approach based on health checks and education. Education was provided on the importance of laboratory tests during pregnancy, the prevention of sexually transmitted infections, and the importance of compliance with routine antenatal check-ups. This activity involved 25 participants, consisting of all pregnant women at Aek Natolu Health Center. The results of the examination showed that out of 25 respondents, 23 respondents (92%) did not have sexually transmitted infections, while 2 respondents (8%) had sexually transmitted infections. The results of this activity show that health laboratory management plays an important role in supporting early detection of sexually transmitted infections in pregnant women, which can serve as a basis for providing education, follow-up, and preventive efforts to improve the quality of maternal and child health services